Aproveitamento da fibra de borra de café como material de reforço em compósitos com matriz de resina epóxi preparada a partir de óleo de cozinha usado - Edna Rocio Triana Tarazona (2017)
The use of natural source materials for the production of biocomposites lead to great interest in industries and researchers due to their low cost, abundance and the fact that they are renewable and biodegradable. In this work, an epoxy matrix was produced from residual soybean oil via peracid formed in situ by heterogeneous catalysis. The produced epoxy matrix was characterized by the determination of the iodine value, oxirane oxygen, viscosity and also by Fourier Transform Infrared Spectroscopy (FTIR). This matrix was subsequently used in the preparation of composites reinforced with spent coffee ground fiber, and a polymerization process was performed with the maleic anhydride as the curing agent without the presence of an accelerator. The spent coffee ground was chemically treated with alkaline hydrogen peroxide in order to decrase the hydrophilicity of the same, and increase interfacial interaction of polymeric composites. The reinforcement was characterized for its infrared composition by Fourier Transform and thermogravimetric analysis. In the composites produced the effects of post-curing time of 5h and 8h, the molar ratio of maleic anhydride 1:1 and 1:1.2 and the mass fraction of the coffee grounds 0%, 20% and 35% were compared by tensile strength, elastic modulus, thermogravimetric analysis, and by physical parameters of bulk density, apparent porosity and water absorption. The results obtained indicated that it was possible to produce an epoxy matrix from the residual soybean oil and to use it as polymeric material in the production of biocomposites reinforced with treated spent coffee ground. The composites made with a mole ratio of maleic anhydride 1: 1,2, post-curing time 8h and mass fraction of 35% were those that presented better mechanical properties of tensile strength and elastic modulus. The addition of a larger quantity of maleic anhydride and longer post-curing time reduced the water absorption and porosity values of the composites.